Role of Transforming Growth Factor Beta in Peripheral Nerve Regeneration: Cellular and Molecular Mechanisms - Ye, Zhiqian; Wei, Junbin; Zhan, Chaoning; Hou, Jin (Frontiers in Neuroscience, 2022)
Peripheral nerve injury (PNI) is one of the most common concerns in trauma patients. Despite significant advances in repair surgeries, the outcome can still be unsatisfactory, resulting in morbidities such as loss of sensory or motor function and reduced quality of life. This highlights the need for more supportive strategies for nerve regrowth and adequate recovery. Multifunctional cytokine transforming growth factor-β (TGF-β) is essential for the development of the nervous system and is known for its neuroprotective functions. Accumulating evidence indicates its involvement in multiple cellular and molecular responses that are critical to peripheral nerve repair. Following PNI, TGF-β is released at the site of injury where it can initiate a series of phenotypic changes in Schwann cells (SCs), modulate immune cells, activate neuronal intrinsic growth capacity, and regulate blood nerve barrier (BNB) permeability, thus enhancing the regeneration of the nerves. Notably, TGF-β has already been applied experimentally in the treatment of PNI. These treatments with encouraging outcomes further demonstrate its regeneration-promoting capacity. Herein, we review the possible roles of TGF-β in peripheral nerve regeneration and discuss the underlying mechanisms, thus providing new cues for better treatment of PNI.